Penerapan Teknik Thumbnail Sketching pada Storyboard Film Animasi "Tingkuluak: Mahkota Perempuan Minang dalam Sehelai Kain - Lauren Arifa; Sheanny Ocmi Sakti (YASIN, 2026)
Although the design of animated film storyboards featuring local cultural themes has developed, studies specifically representing Tingkuluak through thumbnail sketching techniques remain limited. This study aimed to design the storyboard for the animated film “Tingkuluak: Pusaka Perempuan Minang dalam Sehelai Kain” as both a production reference and a medium for Minangkabau cultural education. The study employed a qualitative descriptive design approach supported by simple quantitative data using a Pipeline Animation design. Data were collected through a literature review, an interview with the Chair of Ikatan Bundo Kanduang Kota Padang, questionnaires, documentation, alpha testing, and beta testing involving five respondents. The data were analyzed descriptively through processes of categorization, interpretation, and visual evaluation. The study produced a script, thumbnail sketches, a final storyboard, and an animatic capable of systematically organizing the storyline, visual composition, camera angles, and the presentation of information about Tingkuluak. The beta-testing results yielded a mean score of 4.49 on a five-point scale, with the highest score of 5.00 obtained for suitability as a cultural education medium. These findings indicate that the thumbnail sketching technique supports visual exploration and improves the efficiency of the storyboard design process. This study emphasizes the importance of applying this technique in the development of animated films based on local culture, while also indicating the need for improvements in composition, character expression, transitions, movement, cinematography, and audio to enhance the quality of the production.